African Honey Bee: What You Need to Know - Malcolm T. Sanford; H. Glenn Hall (EDIS)
Several races or subspecies of honey bees reside in Africa. One of these, Apis mellifera scutellata, from the central and southern part of the continent, is the predominant parental type introduced into South America. This is the African or Africanized honey bee so often sensationalized in the media. The European honey bee is the race common to North America, and is an amalgam of many European subspecies imported over the past several centuries. To a much smaller extent, subspecies from Asia and Africa were also introduced.  This document is Fact Sheet ENY-114, a series of the Entomology and Nemotology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Reviewed: March 1995. Revised: September 2005.